Stress Corrosion Cracking Behavior in API 5L Steels for Sour Service - Blanco, A. (Springer, 2022)
This work presents a study on the behavior of stress corrosion cracking (SCC) phenomenon in pipeline steels for sour service in near-neutral media. SCC tests under static stressing conditions were performed in planar steel samples using a Cortest proof-ring coupled with a fabricated cell containing near-neutral pH solution as a corrosive medium, which simulates the soil conditions, to observe the cracking initiation stage. Characterizations of the steel samples using surface techniques such as SEM, EDS, and Raman spectroscopy show that the presence of nonmetallic inclusions takes place as pitting sites (to form corrosion pits), which constitute the most susceptible sites for SCC crack initiation. SEM images taken on the steel sample surfaces exhibit both SCC transgranular and intergranular crack types in near-neutral media. Although the obtained results are interesting, further study is necessary to evaluate and confirm the role of inclusions in SCC initiation mechanisms.